Consumer Involvement and Perceptions of Repositioned Brands - Szylit, Flavia; Isabella, Giuliana; Barros, Lucia Salmonson Guimarães (Revista de Administração da UFSM, 2018)
This study was designed to identify the relationship between consumers’ involvement with a brand, their perception of its repositioning, and their consumption of the brand after repositioning. The object of study, the McDonald’s fast food chain, included healthy items on its menu as part of a bid to reposition its brand. Data were collected via online questionnaires, which were answered by 214 individuals. Data were analyzed using econometrics, resulting in the preparation of a simultaneous equation model with two regressions, whose dependent variables were perception and consumption. The results indicated that perception of brand repositioning depended positively on the consumers’ attitudes towards a balanced diet and how often they frequent McDonald’s, while there was a negative relationship with the consumers’ age, sex, education, and how important they felt the nutritional value of foods was. The results suggest that perception is influenced by personal stimuli and emotional involvement with the brand. However, adherence to the brand after repositioning was not found to be influenced by any kind of involvement, but by the consumers’ personal stimuli.